Analytical methods for auditing and anomaly/fraud detection - Dilia Bernardino; Pedrosa, I.; Laureano, Raul M. S. (2018 13th Iberian Conference on Information Systems and Technologies (CISTI), 2018)
The issue of fraud has recently been more frequent and is a common infraction that can be perpetrated by a single person or arise as a result of collusion, causing asset decrement or theft in organizations. External audits aim to obtain relevant and sufficient evidence that points to high, but not absolute, assurances that the financial statements are free from fraud or material misstatement. On the other hand, the main goal of internal auditing is to identify the risk of fraud by developing strategies that provide the capacity to prevent it and anticipate control needs. Organizations nowadays generate and store more information in electronic format. Because there are large amounts of data, the transactions that are subject of abuse are concealed and harder to detect by traditional means. Thus, analytical methods become increasingly fundamental in identifying and uncovering potential evidence of fraud.